Respuesta :

The solution to given system of equations are (x, y) = (3, -1)

Solution:

Given that we have to solve the system of equations

Given system of equations are:

x = 2y + 5 ------ eqn 1

3y - 3x = -12 --------- eqn 2

We can solve the system of equations by substitution method

Substitute eqn 1 in eqn 2

3y - 3(2y + 5) = -12

3y - 6y - 15 = -12

-3y = 12 + 15

-3y = 3

y = -1

Substitute y = -1 in eqn 1

x = 2(-1) + 5

x = -2 + 5

x = 3

Thus the solution to given system of equations are (x, y) = (3, -1)